The PENGARUH KETERAMPILAN MENGAJAR MENTOR DAN LINGKUNGAN KELUARGA TERHADAP MINAT BELAJAR KEWIRAUSAHAAN - Diwanti, Dyah Pikanthi; Ranto, Dwi Wahyu Pril (PRIMA EKONOMIKA, 2022)
This study aims to determine the effect of mentor teaching skills and family environment on interest in learning entrepreneurship. The population in this study were students of the Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, while the sample was students who had taken entrepreneurship courses. The sampling technique used is purposive sampling. Base on 100 questionnaires distributed, there were 80 respondents who returned the questionnaire and were declared eligible for processing. Data analysis in this study used multiple linear regression analysis. The results showed that students' learning interest in entrepreneurship was influenced by the teaching skills of the mentor and the family environment.